Students’ perceptions and effects of technology integration in English learning: A case study at National University of Battambang - Keo, Vireak; Sam, Rany; lan, Bunrosy; Rouet, Wen (Journal of English and Education (JEE), 2025)
This study investigates the perceptions and effects of first-year students at the National University of Battambang (NUBB) regarding the use of technology in English language instruction. Purposive sampling and a structured questionnaire were used to collect data from 205 students in various majors. The analysis employed descriptive statistics, independent sample t-tests, one-way ANOVA, and regression techniques. Findings revealed that online searching was the most commonly used tool (M=1.47), followed by computer software (M=1.53), while mobile applications were considered the most helpful (M=3.30). These results suggest a generally favorable view of technology's role in enhancing English proficiency. A T-test indicated a significant gender difference (p = 0.034 < 0.05), with female students more likely to engage with technology at lower levels. Although most demographic factors did not show significant variation, age emerged as a factor, with older students reporting greater benefits from technology. Hypothesis testing confirmed a positive link between technology use and improved English learning, with the TSLE variable (H4) having an especially powerful impact (β = 0.063, p = 0.000). The study recommends providing specific support to female students in using technology and promoting diverse digital tools to further enhance language learning.